Perinatal Nutrition Programs the Hypothalamic Melanocortin System in Offspring - Wattez, J.-S.; Delahaye, F.; Lukaszewski, M.-A.; Risold, P.-Y.; Eberlé, D.; Vieau, D.; Breton, C. (Hormone and Metabolic Research, 2013)
Epidemiological studies initially suggested that maternal undernutrition leading to low birth weight may predispose for long-lasting energy balance disorders. High birth weight due to maternal obesity or diabetes, inappropriate early postnatal nutrition, and rapid catch-up growth, may also sensitize to increased risk of obesity. As stated by the Developmental Origin of Health and Disease concept, the perinatal perturbation of fetus/neonate nutrient supply might be a crucial determinant of individual programming of body weight set-point. The hypothalamic melanocortin system composed of the melanocortin receptor 4, its agonist α-melanin-stimulating hormone (α-MSH), and its antagonist agouti-related protein (AgRP) is considered as the main central anorexigenic pathway controlling energy homeostasis. Studies in numerous animal models demonstrated that this system is a prime target of developmental programming by maternal nutritional manipulation. In rodents, the perinatal period of life corresponds largely to the period of brain maturation (i. e., melanocortin neuronal differentiation and development of their neural projections). In contrast, these phenomena essentially take place before birth in bigger mammals. Despite these different developmental time windows, altricial and precocial species share several common offspring programming mechanisms. Offspring from malnourished dams present a hypothalamic melanocortin system with a series of alterations: impaired neurogenesis and neuronal functionality, disorganization of feeding pathways, modified glucose sensing, and leptin/insulin resistance. Overall, these alterations may account for the long-lasting dysregulation of energy balance and obesity. Following maternal malnutrition, hormonal and epigenetic mechanisms might be responsible for melanocortin system programming in offspring.
Keywords: appetite programming; arcuate nucleus; gestation; lactation; gene expression; epigenetic mechanisms